2012
DOI: 10.3382/ps.2010-01050
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prebiotic, protein level, and stocking density on performance, immunity, and stress indicators of broilers

Abstract: An experiment was conducted to determine the effects of period on the performance, immunity, and some stress indicators of broilers fed 2 levels of protein and stocked at a normal or high stocking density. Experimental treatments consisted of a 2 × 2 × 2 factorial arrangement with 2 levels of prebiotic (with or without prebiotic), 2 levels of dietary CP [NRC-recommended or low CP level (85% of NRC-recommended level)], and 2 levels of stocking density (10 birds/m(2) as the normal density or 16 birds/m(2) as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
85
4
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(105 citation statements)
references
References 35 publications
13
85
4
3
Order By: Relevance
“…The results are in accordance with Sohail et al (2013) and Huang et al (2007). Stress reduces the weight of lymphoid organs so it could be postulated that MOS supplementation reduces the heat stress in broilers leading to higher lymphoid organ weight (Houshmand et al 2012). This improved immunity may be due to improved intestinal absorption of some minerals such as Zn, Cu and Se.…”
Section: Methodssupporting
confidence: 76%
See 1 more Smart Citation
“…The results are in accordance with Sohail et al (2013) and Huang et al (2007). Stress reduces the weight of lymphoid organs so it could be postulated that MOS supplementation reduces the heat stress in broilers leading to higher lymphoid organ weight (Houshmand et al 2012). This improved immunity may be due to improved intestinal absorption of some minerals such as Zn, Cu and Se.…”
Section: Methodssupporting
confidence: 76%
“…Dietary supplementation of MOS helps to stabilizes corticosterone level and reduced some of the detrimental effects of heat stress (Sohail et al 2012;Houshmand et al 2012). High environmental temperatures, results in activation of the hypothalamic-pituitary-adrenal axis which leads to elevated a plasma corticosterone concentration, causing deleterious effect (Munck et al 1984).…”
Section: Hematologicalanalysismentioning
confidence: 99%
“…A large number of experiments were carried out to investigate the effects of prebiotic supplementation on growth performance. Some researchers reported that the prebiotic supplementation had no effect on growth performance (Lima et al 2003;Li & Zhang 2007;Houshmand et al 2012), however, some other researchers held opposite views (Yeo & Kim 1997;Mateova et al 2008;Wang & Gu 2010), which were similar to the current experiment. Many researches show that prebiotic in the intestine of animals can grow and reproduce and produce a variety of nutrients such as vitamins, amino acid, some factors of promoting growth, and so on.…”
Section: Effects Of Prebiotic Addition On Serum Biochemical Parametersupporting
confidence: 76%
“…Mortality, leg problems, susceptibility to diseases and behavioural changes were related to stress conditions from overcrowding (Estevez, 2007). Few authors have considered and analysed the effects of overcrowding on the immune system activity of chickens (Dafwang et al, 1987;Heckert et al, 2002;Houshmand et al, 2012). Heckert et al (2002) showed that high stocking densities in broiler chickens decreased the relative weight of the bursa of Fabricius, one of the most important lymphoid organs of chickens, and they related this finding to possible immunosuppression.…”
Section: Introductionmentioning
confidence: 99%